L’image au corps : l’allégorie luxuriante des performances photos chez Annie Baillargeon - Sioui Durand, Guy (Ciel variable, 2006)
Abstract In today's generalized culture of screen images, new "nondisciplines" are entering the visual arts, media arts, action art, and art theory. Digital technologies, in particular, are multiplying in inventiveness and creating experimental zones between images, sound, and text. Art photography oscillates between "reality-fiction," photographic sculptures, and allegorical narrativity. Annie Baillargeon's stunning photomontages luxuriantly construct this third type, the photographic narrative. Inspired by the codes of action art (solo performances and collective movements) and "movie" scenarios (photo and video), her large works revamp the venerable genre of allegory. An elegant mystery floats in her settings, in which she is the body-material and the character with multiple identities. Tension is created between the sacred and the libido in a pop subculture iconoclasm of undefined ethical zones. In fact, allegorical photography such as this, at the beginning of a new millennium, paradoxically speaks to the hermeneutic analytical gaze as art criticism.